Investigating Eleventh Graders' Critical Thinking Skills on Reaction Rate - Muntholib, Muntholib; Khusmawardani, Eli; Yahmin, Yahmin; Rosli, Mohd Shafie (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
Critical thinking skills are high-order thinking skills in which students are required to solve complex problems. The topic of reaction rate has conceptual knowledge, cognitive skills, and psychomotor skills that can be used to assess and develop students' critical thinking skills. This study aims to analyze the critical thinking skills of science eleventh graders on reaction rate. This research applies the survey research method. As the research instrument, it uses a critical thinking skills test on the reaction rate consisting of 27 multiple choice questions with a reliability of 0.756 by involving 153 public senior high school students. The authors develop this test. The results show that the average score of respondents’ critical thinking skills was 33.66 (low category). At the sub-skill level, the average score of respondents' skills in interpreting was 32.73 (low), analyzing was 29.04 (low), inferencing was 36.77 (low), evaluating was 24.61 (low), and explaining was 33.88 (low). This shows that the learning experiences of the students have not been able to develop their critical thinking skills. Therefore, this research suggests the need for a learning strategy that can be used to improve students' critical thinking skills.